Rethinking bridge deck longevity and maintenance with Portland cement polymer concrete - Cramer, Steven; Agosto, Andrew (Midwest Regional University Transportation Center, 2008)
Bridge deck deterioration in the northern Midwest creates significant costs to state Departments of Transportation (DOT?s) in the region. The fundamental cause of the problem is low tensile strength and water permeable reinforced concrete resulting in deck cracking and ultimately reinforcing bar corrosion. Portland Cement Polymer Concrete (PCPC) combined with a design approach tailored to its advantages could virtually eliminate early deck deterioration and the associated costs providing an alternative asset management path for bridge decks. Bridge decks would no longer have to be removed from their substructure every fifteen years and replaced. The results would be higher quality, longer lasting bridge decks with lower life cycle costs. This project will demonstrate the feasibility and methodology of such a strategy. This project will develop a strategy that combines innovative concrete materials, novel design and cost analysis that enhances the longevity and reduces the life cycle cost of highway bridge decks. The project is expected to show significant life-cycle cost advantages to using a high performance bridge deck material.
111 p.
Keywords: Bridge decks; Bridge maintenance; Concrete; Life cycle costing; Polymers; Portland cement; Service life; Tensile strength